Penyelarasan Peraturan Perundang-Undangan Sebagai Langkah Reformasi Hukum di Indonesia - Jaga Rudi (Universitas Maritim AMNI Semarang, 2023)
Indonesia is a state of law. every element of the life of the nation and state is regulated by law. problems then arise, because as a state of law that has many rules the problem of over regulation cannot be avoided. Coupled with the disharmonisation of legislation makes the problem more complicated. Of course, the stages of the formation of laws and regulations must pay attention to the principles that have prevailed in the previous provisions. The presence of institutions for harmonisation is also needed in this case. In this paper, the author uses normative juridical research, which is a study of approaches to laws and regulations which are then elaborated by examining several literature materials so as to obtain results regarding the harmonisation of laws and regulations.